AVALIAÇÃO DE MATÉRIAS-PRIMAS PARA QUALIDADE DE BIODIESEIS PELA PREDIÇÃO DE PROPRIEDADES FÍSICO-QUÍMICAS - Barradas Filho, Alex Oliveira (2015)
Alternative fuels have the potential to replace gradually the petroleum derivatives, and the biodiesel, that is a biofuel obtained from transesterification of triglycerides, is pointed as a substitute for mineral diesel. The present work focus on the optimization and application of artificial neural networks (ANNs) on the prediction of viscosity, iodine value, induction period, cetane number, specific gravity and cold filter plugging point of biodiesel, which are properties inherent to the composition. The input variables were the percentage of 13 fatty acid methyl esters (FAMEs) more common in biodiesels and, once the transesterification does not modify the fatty esters profile of the raw materials, the ANN method allowed the prediction of the six properties, even before the transesterification, after synthesis of the biodiesel or during the storage. Therefore, this method can be useful as a tool to evaluate the potential of raw materials to produce a biodiesel with good quality and to reach improvements on official methods. The optimization process of ANN occurred in three steps: test of algorithms for adjusting weights, test of stopping condition and test of activation functions, and the physicochemical properties were treated independently. For the set of test samples, which simulates real samples, the application of the optimized ANNs provided results with root mean squared errors (RMSE) of 0.55 mm²/s, 3.49 g/100g, 0.89 h, 2.06, 2.89 kg/m³ and 2.61 °C for viscosity, iodine value, induction period, cetane number, specific gravity and cold filter plugging point, respectively, what ensures the feasibility of the proposed method. A comparison between the proposed method and linear methods from literature, both based on the biodiesel composition indicate that our ANN model is much more adequate to the problem addressed.